아질산염 소거 작용을 가진 산채 혼합물을 함유한 김치의 항산화 활성 및 산화적 신경세포 사멸 억제 효과 - 강경훈(Kyung Hun Kang); 박시영(Si Young Park); 권기한(Ki Han Kwon); 임희경(Heekyung Lim); 김성현(Sung Hyun Kim); 김정균(Jeong Gyun Kim); 정미자(Mi Ja Chung) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2015)
This study was carried out to investigate the nitrite scavenging activities (NSA) of nine kinds of wild vegetables in a $NaNO_2$ model system and nitrite of Chinese cabbage as well as the inhibitory effect of kimchi containing a mixture of wild vegetables (MWV) with nitrite scavenging activity on brain neuronal cell death. NSA was higher at pH 1.2 than pH 4.2 in all samples. NSA of extracts from sprouts of Oenothera laciniata and Aster scaber (AS) was above 90% at pH 1.2. AS, Codonopsis lanceolate (CL), Adenophora triphylla (AT), Platycodon grandiflorum (PG), and Taraxacum officinale (TO) extracts showed significantly higher levels of NSA than those from other extracts at pH 4.2. CL, AT, PG, and TO extracts showed high NSA on nitrite of Chinese cabbage. In addition, the effects of MWV on antioxidant and brain neuronal cell death induced by oxidative stress were investigated in human brain neuroblastoma SK-N-SH cells. MWV extract attenuated $H_2O_2$-induced cell death and reactive oxygen species (ROS) generation in SK-N-SH cells. MWV extract showed significantly higher DPPH radical scavenger activity when compared to normal kimchi extract. MWV extract showed an inhibitory effect on brain neuronal cell death against oxidative stress by antioxidant activities. 본 연구에서는 $NaNO_2$ 모델계와 배추에 함유된 아질산염에 대한 9종류 산채들의 아질산염 소거 작용 및 아질산염 소거 작용을 가진 산채들의 혼합물을 함유한 김치(MWV)의 뇌신경세포 사멸 억제 효과에 대해 연구하였다. 아질산염 소거 작용은 모든 시료에서 pH 4.2에서보다 pH 1.2에서 높았고, 다래순 추출물과 참취 추출물(AS)은 pH 1.2에서 90% 이상 아질산염 소거 작용을 나타내었다. AS, 더덕, 잔대, 도라지 및 민들레 추출물들(CL, AT, PG, TO)은 pH 4.2에서 다른 추출물보다 아질산염 소거 작용이 높았다. CL, AT, PG 및 TO는 배추에 함유된 아질산염에 대해 높은 아질산염 소거 작용을 가지고 있었다. 더하여 항산화 및 산화적 스트레스에 의한 뇌신경세포 사멸에 대한 MWV의 영향을 사람의 뇌 신경모세포종 SK-N-SH 세포 내에서 연구하였다. MWV 추출물은 SK-N-SH 세포에서 $H_2O_2$에 의해 유도된 세포 사멸과 ROS 생성을 약화시켰다. MWV 추출물은 일반김치 추출물과 비교하여 현저하게 높은 DPPH 라디칼 소거 작용을 보여주었다. MWV 추출물은 항산화 효과에 의해 산화적 스트레스($H_2O_2$)에 대항하여 뇌신경세포 사멸 억제 효과를 가지고 있었다.